Effect of irrigation and fertilization on some chemical characteristics of a Vertisol - Pereira, José Ribamar; Cordeiro, Gilberto Gomes (Pesquisa Agropecuaria Brasileira, 2014)
The effect of irrigation and fertilizer applied annually for 17 years was evaluated for some chemical characteristics of a Vertisol cultivated with grapevine. The water was applied through a border irrigation system. The fertilizers were broadcasted between the rows of vines and incorporated into the soil up to a depth of 5cm. The soil samples were collected from 18 points of the cultivated area and from seven points of the virgin soil, around the grapevine orchard, at depths of 0-15 cm, 15-30 cm, 30-60 cm, 60-90 cm e 90-120 cm. The analytical results showed that practically there were no perceptible variations in the amount of exchangeable Ca2+, Mg2+ and Na+, organic matter, N-NH+4, and Zn in relation to virgin soil. Concerning the other parameters it was observed that in the upper layers there was a decrease of the pH and an increase of the electrical conductivity (EC) and of exchangeable K+, P, total N, N-NO-3, Cu, Mn and Fe. These differences, however, decreased with the depth except for Fe. Higher concentration of Cu and Mn should have been consequence of the annual application of fungicide and/or solubilization of compounds containing these elements. The results obtained indicate that the changes observed in some parameters, as a result of the application of irrigation water and fertilizers to the soil, should not interfere with the yield capacity of the soil.